Effectiveness of Work Motivation on Employee Performance at the Faculty of Economics and Islamic Business - Aprillia, Hendra Safira; Nuraini, Intan Ayu; Hanafirafif, Unedo Daffa Muafa (Journal of Economic, Religious, and Entrepreneurship (JoERE), 2024)
Work motivation is an internal and external drive that encourages     a     person     to     improve     the     quality     of     their performance. The right motivational factors can realize productive performance so that work becomes more effective and efficient. This study aims to identify the effectiveness of work motivation in improving staff performance in academic units with work environment characteristics based on Islamic higher education administration. This research uses descriptive qualitative methods through interviews and literature review. The results revealed various work motivation factors that contribute to staff satisfaction, performance improvement and productivity. Good motivation, self-development opportunities, and employee engagement proved to play an important role in creating job satisfaction in the academic environment.